Design of the Public Complaint Application for the Office of Public Works and Housing Department of Langkat Regency, North Sumatra - Lubis, Zuheri; Ramadani , Fiqih Qodri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
To date, the Langkat Regency Government still has to go to the PRPU office to complain from the public. This method of complaint will certainly take a little time and take a little time. Public complaint data is not stored as evaluation or preparation material for BAPPEDA. Information conveyed by the district government also takes a long time to reach the community. Even though basically now there is WhatsApp, people can also use WhatsApp messages to send evidence of incidents and so on. However, the complaint message will not be stored in its entirety, even several days after the message is received, it will easily be overwritten by other messages, making it difficult to find again. In connection with this problem, the researchers tried to design an application entitled Langkat Regency Community Complaints. In designing this application, the author used the Waterfall model SDLC method, which was carried out step by step according to the procedures in the Waterfall method. By producing a public complaints application, it can facilitate the process of managing and resolving public complaints at the Langkat Regency Public Works and Public Housing Service.